A Cognitive-Perceptual Approach to Conceptualizing Speech Intelligibility Deficits and Remediation Practice in Hypokinetic Dysarthria - Kaitlin L. Lansford; Julie M. Liss; John N. Caviness; Rene L. Utianski (Parkinson's Disease)
Hypokinetic dysarthria is a common manifestation of Parkinson's disease, which negatively influences quality of life. Behavioral techniques that aim to improve speech intelligibility constitute the bulk of intervention strategies for this population, as the dysarthria does not often respond vigorously to medical interventions. Although several case and group studies generally support the efficacy of behavioral treatment, much work remains to establish a rigorous evidence base. This absence of definitive research leaves both the speech-language pathologist and referring physician with the task of determining the feasibility and nature of therapy for intelligibility remediation in PD. The purpose of this paper is to introduce a novel framework for medical practitioners in which to conceptualize and justify potential targets for speech remediation. The most commonly targeted deficits (e.g., speaking rate and vocal loudness) can be supported by this approach, as well as underutilized and novel treatment targets that aim at the listener's perceptual skills.